Study on the New Principle of Transformation Heat into Electricity - Skornyakov, G. V. (Research Trends and Challenges in Physical Science Vol. 5, 2021)
The general scheme of heat-to-electric power conversion in closed thermally inhomogeneous heterogeneous flow with constantly renewable local imbalance is considered. Conversion system comprises high-speed motor-generator rigidly coupled with propulsor. Propulsor has the form of rotating vessel containing liquid phase of working substance. Nozzles are installed on it to discharge liquid into closed volume filled with gas. The jet of working substance leaving the propulsor under the action of high pressure due to centrifugal forces is directed in the opposite direction of rotation of the generator, but its phase composition and other thermodynamic parameters are not determined. The transition of the working substance from the propulsor to the closed volume goes beyond equilibrium thermodynamics. Motion energy of each element of working substance mass leaving the propulsor is supplied to electric power generation. The rapid transition of the accelerated compressed liquid to the low gas pressure region and its shutdown lead to "self-cooling" of the working substance.